1993
DOI: 10.1111/j.1745-4549.1993.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

DIFFUSION of LOW-MOLECULAR COMPOUNDS IN FOOD MODEL SYSTEMS

Abstract: The diffusion of NaCl and isopropanol was studied in a matrix of pure gel and one containing either carbohydrates, proteins or fat using the concentration‐distance method. Concentrations of NaCl were measured by conductivity, those of isopropanol by gas chromatography. Diffusion experiments have shown that the temperature dependence of the diffusion coefficient is in accordance with an Arrhenius approach. Experimental and predicted diffusion coefficients didnot agree satisfactorily when only models of mere obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The partition coefficient represents the affinity of the matrix for NaCl or the other solutes. We can therefore conclude that as the water/product partition coefficient determined by the SL-PRV method in model cheese was not equal to 1, interactions between NaCl and other matrix component, such as caseins, exist (Diaz et al, 1993). These results revealed that the SL-PRV method allows a good estimation of the partition coefficient and initial concentration.…”
Section: Determination Of Partition and Diffusionmentioning
confidence: 61%
“…The partition coefficient represents the affinity of the matrix for NaCl or the other solutes. We can therefore conclude that as the water/product partition coefficient determined by the SL-PRV method in model cheese was not equal to 1, interactions between NaCl and other matrix component, such as caseins, exist (Diaz et al, 1993). These results revealed that the SL-PRV method allows a good estimation of the partition coefficient and initial concentration.…”
Section: Determination Of Partition and Diffusionmentioning
confidence: 61%
“…, 2000b, 2001). The rate of salt diffusion is temperature dependent and it increases with increasing temperature (4–40 °C) (Diaz et al. , 1993; Corzo & Bracho, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial shrinkage of the muscle fibres during dry and brine salting of Atlantic salmon fillets has been reported (Sigurgisladottir et al, 2000b(Sigurgisladottir et al, , 2001. The rate of salt diffusion is temperature dependent and it increases with increasing temperature (4-40°C) (Diaz et al, 1993;Corzo & Bracho, 2004). The salt diffusivity during curing of salmon fillets is strongly concentration (Wang et al, 1998a), and temperature dependent (Chiralt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in polymer concentration may influence the diffusion rate of substances, the pore size of the gel, and the mechanical hindrance exerted by the structural components of the network structure. At first, it should be mentioned that several researchers have reported that in agar gels the diffusion rate of low molecular weight (MW) substances, such as glucose and low MW proteins, is practically unaffected by polymer concentration (Diaz, Wolf, Kostaropoulos, & Spiess, 1993;Stecchini et al, 1998). They also concluded that the diffusion does depend on the pore size of the gel and the molecular weight of the diffusing substances.…”
Section: Effect Of Glucosementioning
confidence: 99%